Gut microbes metabolize strawberry phytochemicals and mediate their beneficial effects on vascular inflammation - Chrissa Petersen; Adhini Kuppuswamy Satheesh Babu; Ceres Mattos Della Lucia; Henry A. Paz; Lisard Iglesias-Carres; Ying Zhong; Thunder Jalili; J David Symons; Kartik Shankar; Andrew P. Neilson; Umesh D. Wankhade; Pon Velayutham Anandh Babu (Gut Microbes)
Evidence suggests that a healthy gut microbiome is essential for metabolizing dietary phytochemicals. However, the microbiome’s role in metabolite production and the influence of gut dysbiosis on this process remain unclear. Further, studies on the relationship among gut microbes, metabolites, and biological activities of phytochemicals are limited. We addressed this knowledge gap using strawberry phytochemicals as a model. C57BL/6J mice were fed a standard diet [C]; strawberry-supplemented diet (~2 human servings) [CS]; strawberry-supplemented diet and treated with antibiotics (to deplete gut microbes) [CSA]; high-fat diet (HFD) [HF]; strawberry-supplemented HFD [HS]; and strawberry-supplemented HFD and treated with antibiotics [HSA] for 12 weeks. First, antibiotic treatment suppressed the production of selected metabolites (CSA vs. CS), and p-coumaric acid was identified as a strawberry-derived microbial metabolite. Second, HFD-induced dysbiosis negatively affected metabolite production (HS vs. HF), and hippuric acid was identified as a microbial metabolite in HFD conditions. Third, dietary strawberries improved HFD-induced vascular inflammation (HS vs. HF). However, antibiotic treatment reduced metabolite production and abolished the vascular effects of strawberries (HSA vs. HS), indicating the importance of gut microbes in mediating the vascular benefits of strawberries via metabolites. Fourth, strawberry supplementation decreased Coprobacillus that was positively associated with vascular inflammation, whereas it increased Lachnospiraceae that was negatively associated with vascular inflammation and positively associated with hippuric acid. Fifth, hippuric acid was negatively associated with vascular inflammation. Our study fills in some pieces of the giant puzzle regarding the influence of gut microbes on the biological activities of phytochemicals. HFD-induced gut dysbiosis negatively impacts metabolite production and a strong association exists among gut microbes, strawberry-derived microbial metabolites, and the vascular benefits of dietary strawberries. Further, our study provides significant proof of concept to warrant future research on the use of strawberries as a nutritional strategy to prevent vascular complications.